A relação entre compreensão leitora, conhecimento e integração léxico-semântica - Sousa, Lucilene Bender de (2015)
Reading is one of the main ways of acquiring knowledge. Initially, children learn to read and then they read to learn, for this reason literacy is one of the central goals of formal education. However, it is acknowledgeable that a lot of students have serious reading problems at the end of Elementary School. National research has concentrated efforts in investigating literacy problems, but little research has been dedicated to the study of reading comprehension difficulties. Towards this need, this thesis aims at investigating the relationship between reading comprehension, lexical-semantic knowledge and integration in students from public schools at the end of the Elementary education. Although some students still have problems with word reading at the last year of school, their major challenge is text comprehension, since it interferes with performance in all school subjects. But why do not some readers, despite their good decoding skill, understand what they read? Research points to the possibility of a lexical-semantic deficit in poor comprehenders (NATION; SNOWLING, 1998; PERFETTI; HART, 2002). Based on this assumption, three studies were conducted: Study A inquired into the depth of vocabulary knowledge, implicit semantic memory and lexical-semantic processing skill of good and poor comprehenders; study B examined the group’s performance in two tasks requiring lexical-semantic integration; and study C investigated whether poor comprehenders provide better response to comprehension questions when they are preceded by a glossary and a lexical-semantic integration task. The results confirmed the lexical-semantic deficit hypothesis since the depth of vocabulary knowledge as well as the ability of word-to-text integration were significantly inferior in poor comprehenders as compared to good ones. Nevertheless, the results did not corroborate implicit memory differences as both groups benefited from lexical-semantic integration task followed by a glossary, as well as from a global integration task before answering comprehension questions; they exhibited better comprehension in these tasks when compared to a control one. This thesis contributes to reading comprehension difficulties research, especially in Brazil, where this study field is still underdeveloped. Moreover, it urges the discussion on possible pedagogical interventions, serving as a reference for teachers that seek to understand their students’ reading comprehension difficulties and help them.